Pyrrolophthalazine dione (PPD)-based donor–acceptor polymers as high performance electrochromic materials. Issue 9 (16th December 2014) - Ye, Qun; Neo, Wei Teng; Lin, Tingting; Song, Jing; Yan, Hong; Zhou, Hui; Shah, Kwok Wei; Chua, Soo Jin; Xu, Jianwei
Abstract : Novel solution-processable pyrrolophthalazine dione-containing electrochromic conjugated polymers with high optical contrast, high coloration efficiency, and good long-term stability were reported. Abstract : A novel pyrrolophthalazine dione (PPD) acceptor was sophisticatedly designed and synthesized via an inverse electron demand Diels–Alder reaction, followed by aromatization with N -bromosuccinimide. The PPD moiety was incorporated into donor–acceptor type conjugated polymers through Stille coupling polymerization to yield a series of polymersP1–P3 with different linking groups, namely, thiophene, thieno[3, 2- b ]thiophene, and bithiophene. The polymers reveal excellent solubility in common organic solvents. Due to their low bandgaps of around 1.72–1.78 eV, the polymers show broad absorption that covers most of the visible region. All the polymers reveal electrochromism, switching between dark blue and transmissive sky blue states. In particular, P2 exhibits exceptional electrochromic properties with high optical contrasts of up to 34 and 71% in the visible and NIR regions, high coloration efficiencies of 471 and 651 cm 2 C −1 respectively, as well as reasonable switching speeds and good long-term stability.